Lobaric acid and pseudodepsidones inhibit NF-κB signaling pathway by activation of PPAR-γ. Issue 22 (1st December 2018) - Carpentier, Claudia; Barbeau, Xavier; Azelmat, Jabrane; Vaillancourt, Katy; Grenier, Daniel; Lagüe, Patrick; Voyer, Normand
Graphical abstract: Abstract: Herein we report the anti-inflammatory activity of lobaric acid and pseudodepsidones isolated from the nordic lichen Stereocaulon paschale . Lobaric acid (1 ) and three compounds (2, 7 and9 ) were found to inhibit the NF-κB activation and the secretion of pro-inflammatory cytokines (IL-1β and TNF-α) in LPS-stimulated macrophages. Inhibition and docking simulation experiments provided evidence that lobaric acid and pseudodepsidones bind to PPAR-γ between helix H3 and the beta sheet, similarly to partial PPAR-γ agonists. These findings suggest that lobaric acid and pseudodepsidones reduce the expression of pro-inflammatory cytokines by blocking the NF-κB pathway via the activation of PPAR-γ.